Multi-generation study of heavy ion beam-induced mutations and agronomic trait variations to accelerate rice breeding - Ren, Weibin; Wang, He; Du, Yan; Li, Yan; Feng, Zhuo; Zhou, Xinhui; Kang, Guisen; Shu, Qingyao; Guo, Tao; Guo, Huijun; Yu, Lixia; Jin, Wenjie; et al. (Frontiers in Plant Science, 2023)
Heavy ion beam (HIB) is an effective physical mutagen that has been widely used in plant mutational breeding. Systemic knowledge of the effects caused by different HIB doses at developmental and genomic levels will facilitate efficient breeding for crops. Here we examined the effects of HIB systematically. Kitaake rice seeds were irradiated by ten doses of carbon ion beams (CIB, 25 – 300 Gy), which is the most widely used HIB. We initially examined the growth, development and photosynthetic parameters of the M1 population and found that doses exceeding 125 Gy caused significant physiological damages to rice. Subsequently, we analyzed the genomic variations in 179 M2 individuals from six treatments (25 – 150 Gy) via whole-genome sequencing (WGS). The mutation rate peaks at 100 Gy (2.66×10-7 / bp). Importantly, we found that mutations shared among different panicles of the same M1 individual are at low ratios, validating the hypothesis that different panicles may be derived from different progenitor cells. Furthermore, we isolated 129 mutants with distinct phenotypic variations, including changes in agronomic traits, from 11,720 M2 plants, accounting for a 1.1 % mutation rate. Among them, about 50 % possess stable inheritance in M3. WGS data of 11 stable M4 mutants, including three lines with higher yields, reveal their genomic mutational profiles and candidate genes. Our results demonstrate that HIB is an effective tool that facilitates breeding, that the optimal dose range for rice is 67 – 90 % median lethal dose (LD50), and that the mutants isolated here can be further used for functional genomic research, genetic analysis, and breeding.